Respuesta :

On Solving, we get the points (11/13, -17/13).

Given :-  Two equations as,

               [tex] 9x + 2y -5= 0 ...............(1)\\ \\ \\ y - 2x + 3 = 0 ..............(2) [/tex]

We will express Y in terms of X here.

In first equation we put the value of   y = 2x +3 then expression will be

                 [tex] 9x + 2(2x - 3) = 5 .................(3)[/tex]

The value of x from the equation (3) will be x= 11/13 then, the value of y will be

                 [tex] y = 2(11/13) - 3 = -17/13[/tex]

Therefore, The solution algebraically is (11/13, -17/13).

Learn more about Algebraic equation here : https://brainly.com/question/953809

ACCESS MORE